Effect of intermittent fasting on fat mass and fat free mass among obese adult: A literature review - Hadiyati Fudla; Ninik Mudjihartini; Helda Khusun (Indonesian Nutrition Association, 2021)
Introduction Obesity is a serious hurdle facing by the world nowadays. Even though so many efforts have been done, yet the prevalence is keep rising. Intermittent fasting is seen as an effective and optimal approach for improving nutrition status without undesirable side effect. Objective to identify the effect of intermittent fasting on fat mass and fat free mass among obese adult. Methods: a literature exploration was conducted from January to October 2020 by searching the relevant studies from several databases. Results: many human clinical trials recommended that IF affects beneficial on body composition and body weight. Consuming calorie only in a certain time frame per day for 4-12 months put the body into a fast metabolism which influence the reduction of fat mass from 0.03–16.4% intervention and increasing of fat free mass for around 0.64 to 0.86%. Conclusion: intermittent fasting may reduce fat mass and increase fat free mass in obese adult through the reduction of energy intake (fasting) and the benefit to adipose tissue, liver, pancreas, skeletal muscle, and the brain.